An Efficient Promising Direction for the Synthesis of Dispirotripiperazine (6-6-6 DSTP) Core - Golmohammadi, Mahsa; Pesyan, Nader Noroozi; Şahin, Ertan (Synthesis, 2024)
A new and facile route for the one-pot synthesis of 3,12-dicyano-3,6,9,12-tetraazadispiro[5.2.59.26]hexadecane-6,9-diium dibromide as a dispirotripiperazine source was introduced by the simple reaction of 1,4-diazabicyclo[2.2.2]octane (DABCO) with cyanogen bromide (BrCN) under mild condition at room temperature. The hydrolysis of dicyanamide moieties in the prepared dispiro compound gave 3,12-diaza-6,9-diazoniadispiro[5.2.5.2]hexadecane dibromide with the dispirotripiperazine (6-6-6) core. The molecular structure of the new compound was characterized by FT-IR, 1H, 13C, HSQC NMR spectroscopy, mass and CHN analysis, and X-ray crystallography technique.
Keywords: dispirotripiperazine; cyanogen bromide; DABCO; (6-6-6) DSTP; one pot